A Drone-Based 0.7-4.7 GHz FMCW Radar System for High-Resolution Exploration of Subsurface Glacier Structures - Stelzig, Michael; Benedikter, Andreas; Kleinlein, Micha; Haberberger, Niklas; Krabbe, Lena; Lomakin, Konstantin; Braun, Matthias; Krieger, Gerhard; Vossiek, Martin (2023 IEEE International Radar Conference (RADAR), 2023)
A majority of the studies on subglacial structure mapping and imaging have relied on low-frequency ground penetrating radar (GPR) systems. In particular, mapping alpine glaciers using surface-based high-resolution radar sensors poses a considerable threat to the operators due to crevasses or avalanches; this can be avoided by deploying an unpiloted aerial vehicle (UAV)-based radar sensor. Herein, we present an ultrawideband (UWB) bistatic frequency-modulated continuous-wave (FMCW) GPR for operation on a UAV. By using a UAV equipped with ultrawideband and extremely lightweight additively manufactured horn antennas at a bandwidth of 4GHz between 0.7 GHz and 4.7 GHz we acquired ultra-high-resolution images of the upper firn layers of an alpine glacier. The acquired measurements at the Jungfraufirn, Switzerland illustrate the out-standing performance of the overall system and its applicability in glaciological research.<br
Keywords: Ground penetrating radar; Horn antennas; Radar; Bandwidth; Radar imaging; Radar antennas; Autonomous aerial vehicles; Unpiloted Aerial Vehicle; Frequency-Modulated Continuous-Wave Radar; Horn Antenna; Subsurface Imaging; Glacial Exploration; Ground Penetrating Radar

A Joint Radar and Communication Approach Based on Phase-Coded FMCW Chirp Sequences - Alami El Dine, Mohamad; Stelzig, Michael; Schür, Jan; Vossiek, Martin (International Conference on Microwaves for Intelligent Mobility (ICMIM), 2024)
Joint radar and communication (RadCom) systems are an emerging solution to the spectrum congestion problem that has attracted the attention of both scientific and industrial researchers—for example, in the field of autonomous systems. In this contribution, we propose a novel signaling approach utilizing a chirp sequence radar to seamlessly integrate communication capabilities into the system. The concept relies on a correlation-based synchronization and can estimate and compensate phase errors caused by Doppler frequency shifts in the received signals. Measurement results at 25-GHz confirmed the system’s simulated performance.<br
CRIS-Team Scopus Importer:2024-09-06
Keywords: Chirp sequence; PC-FMCW; RadCom.

A Pseudo-Random Noise-Coded 1.35 GHz Sequential Sampling Impulse Radar System for Forefield Reconnaissance for Ice Exploration Melting Probes - Haberberger, Niklas; Stelzig, Michael; Krabbe, Lena; Hehn, Markus; Vossiek, Martin (2024 21st European Radar Conference (EuRAD), 2024)
Presented in this study is a sequential sampling impulse radar (SSIR) system with pseudo-random noise (PRN) coding designed for forefield reconnaissance for melting probes, enabling the subsurface exploration of icy moons, such as Europa and Enceladus. Characterized by simple hardware and a compact form factor, the developed multi-channel SSIR utilizes pseudo-random noise sequences to effectively enhance the signal-to-noise ratio (SNR). Demonstrating exceptional sensitivity and performance, a prototype system was tested on the Langenferner glacier in Ital

A Radar and Sonar-Based Hybrid Forefield Reconnaissance System for Melting Probes for Englacial Exploration - Stelzig, Michael; Haberberger, Niklas; Audehm, Jan; Becker, Fabian; Nghê, Chi Thanh; Ellinger, Enrico; Do, Mia; Krabbe, Lena; Heinen, Dirk; Zierke, Simon; Böck, Georg; Helbing, Klaus; et al. (IEEE Transactions on Geoscience and Remote Sensing, 2024)
The polar regions of Mars as well as the ice-covered moons such as Saturn’s Enceladus and Jupiter’s Europa have emerged as significant targets for ongoing and future space missions focused on investigating potentially habitable celestial bodies within our solar system. A key objective of these missions is to explore subglacial water reservoirs lying beneath the ice crusts of moons, such as Europa. The utilization of melting probes shows immense promise for achieving this goal. However, in addition to the capability to melt through the ice body, such a probe must also be able to identify the ice–water interface as well as obstacles in its path, such as cavities or meteoric rocks. To address these challenges, we present a forefield reconnaissance system (FRS) featuring a hybrid sensing approach that combines radar and sonar both integrated into the tip of a melting probe. Furthermore, the system includes an in situ permittivity sensor to ensure accurate radar range assignment and to gather scientific data about the ice body. The system has been integrated into a demonstrator melting probe and tested in a terrestrial analog scenario. Measurements at the Jungfraufirn in Switzerland confirm the potential of the developed system.<br
Keywords: Probes; Radar; Reservoirs; Sonar; Heating systems; Snow; Permittivity; Radar System; Solar System; Thermal Conductivity; Dielectric Constant; Autonomous Vehicles; Acoustic Signals; Inertial Measurement Unit; Vector Network Analyzer; Phase-locked Loop; Simultaneous Localization And Mapping; Planar Antenna; Gallium Nitride; Robot Operating System; Ground Penetrating Radar; Aluminum Nitride; Coaxial Line; German Aerospace Center; High Power Amplifier; Protection Circuit; Outer Conductor; Relative Permittivity Values; Acoustic Transducer; Extraterrestrial Life; Binary Phase Shift Keying; Stray Field; Echo Signal; Test Locations; Antenna Array; Radar Measurements; Equivalent Circuit

A Synthetic Aperture Imaging Concept for a Sequential Sampling Impulse Radar - Krabbe, Lena; Haberberger, Niklas; Stelzig, Michael; Hehn, Markus; Vossiek, Martin (German Microwave Conference (GeMiC), 2024)
Sequential sampling impulse radar, which is known for its low complexity and potential energy efficiency, has seen limited exploration of its imaging capabilities, particularly for synthetic aperture radar (SAR) focusing. This paper fills this gap by introducing a phase-based SAR imaging concept for a sequential sampling impulse radar without IQ-mixer. This work outlines a mathematical model for the received echo signal and processing steps to extract the phase information from the real-valued radar data. Experimental validation is performed in an outdoor scenario. The measurement results demonstrate successful phase-based SAR focusing, overcoming the limitations of amplitude-based reconstruction. The signal processing and imaging concept shown in this paper, combined with the used 1.35 GHz sequential sampling impulse radar systems, is intended for future use in glaciological research for the enhanced monitoring of glacier stratification, but it is also suitable for many other high-resolution ground penetrating radar (GPR) applications.<br
Keywords: synthetic aperture radar; sequential sampling impulse radar; switched oscillators; backprojection

A Tutorial on the Sequential Sampling Impulse Radar Concept and Selected Applications - Vossiek, Martin; Haberberger, Niklas; Krabbe, Lena; Hehn, Markus; Carlowitz, Christian; Stelzig, Michael (IEEE Journal of Microwaves, 2023)
The sequential sampling impulse radar is a radar concept that has been known for a very long time. Ultrawideband (UWB) radar systems have been realized based on this concept long before the popular phrases UWB and UWB radar were created. Its hardware simplicity, low cost, potentially high bandwidth and high range resolution, as well as the unsurpassed low power consumption of some of its variants have made it one of the most widely used radar concepts in industrial automation today. Despite its widespread use in practice, however, there are only few publications, textbooks and tutorials that describe this concept in detail and all its varieties and aspects. Especially, the correlation properties and the resulting signal-tonoise ratio (SNR), as well as the phase injection locking of pulsed oscillators, that is required for powerefficient options, have rarely been described in detail. This tutorial introduces the typical sequential sampling impulse radar concept step by step and presents the characteristics and pros and cons. As for the correlation properties and the SNR, the concepts are compared to those of standard coherent impulse radar systems and of frequency modulated continuous wave (FMCW) radar. In addition to the system theory, selected applications are presented to illustrate the attractiveness and elegance, but also the limits, of this interesting and important radar concept. The shown applications range from those in the main field of use of this type of radar, that is, industrial automation, to former and current radar concepts in the areas of automotive radar, ground penetrating radar (GPR), security scanners, and biomedical radar system
Keywords: Ground penetrating radar; Power demand; Costs; Radar measurements; Tutorials; Radar imaging; Radar tracking

A UAV-based Radar Sounder SAR System for the Imaging of Internal Snow and Firn Stratifications - Stelzig, Michael; Benedikter, Andreas; Krabbe, Lena; Schultz, Jakob; Haberberger, Niklas; Braun, Matthias; Krieger, Gerhard; Vossiek, Martin (Proceedings of the European Conference on Synthetic Aperture Radar, EUSAR, 2024)
Unpiloted aerial vehicle (UAV)-based synthetic aperture radars (SAR) offer great potential for use in the structural mapping of snow and firn structures, such as crevasses or stratifications within the subsurface of alpine glaciers. Especially advantageous is the possibility to conduct autonomous and wide-area measurements of a glacier without the risk of crevasse fall or avalanches for ground-penetrating radar (GPR) operators. We present an imaging approach for the mapping of snow and firn structures based on a UAV-borne GPR system, capable of precisely accommodating the refraction effects at the surface. Several common methods for estimating the refraction at the dielectric interface for a planar surface are presented, and their performance is evaluated. As the topography of an alpine glacier is rarely planar, an imaging approach for arbitrary surfaces is presented, which relies on the extraction of the surface from the raw radar B-scan. Measurements from a sand pit experiment confirm the applicability of the imaging approach before the algorithm is applied to measurements from the Jungfraufirn glacier, Switzerland, highlighting the great potential of UAV-based GPR for use in future glacial research.
CRIS-Team Scopus Importer:2024-05-31

Concept for an Automatic Annotation of Automotive Radar Data Using AI-segmented Aerial Camera Images - Hoffmann, Marcel; Braun, Sandro; Sura, Oliver; Stelzig, Michael; Schüßler, Christian; Graichen, Knut; Vossiek, Martin (Proceedings of the IEEE Radar Conference, 2023)
This paper presents an approach to automatically annotate automotive radar data with AI-segmented aerial camera images. For this, the images of an unmanned aerial vehicle (UAV) above a radar vehicle are panoptically segmented and mapped in the ground plane onto the radar images. The detected instances and segments in the camera image can then be applied directly as labels for the radar data. Owing to the advantageous bird's eye position, the UAV camera does not suffer from optical occlusion and is capable of creating annotations within the complete field of view of the radar. The effectiveness and scalability are demonstrated in measurements, where 589 pedestrians in the radar data were automatically labeled within 2 minutes.
Created from Fastlane, Scopus look-up
Keywords: Automotive radar; data annotation; image segmentation; machine learning; sensor fusion

Experimental Verification of a Digital Delay Transponder Used as an In-Ice Synthetic Aperture Radar Reference Target - Stelzig, Michael; Benedikter, Andreas; Horn, Ralf; Jaeger, Marc; Keller, Martin; Scheiber, Rolf; Haberberger, Niklas; Krabbe, Lena; Krieger, Gerhard; Vossiek, Martin (2023 53rd European Microwave Conference (EuMC), 2023)
Low-frequency radar systems offer great potential to support navigation systems of exploratory ice-penetrating probes for cryospheric applications. Due to the comparably small radar cross-section (RCS) of such probes, transponder-like functionalities are mandatory to realise an increased RCS for a reliable in-ice detection and localisation of these probes. To support such applications, a miniaturised monostatic digital delay transponder was developed and tested in a measurement scenario with an airborne synthetic aperture radar (SAR) sensor on an alpine glacier.<br
Keywords: Radar cross-sections; Prototypes; Tomography; Signal processing; Delays; Radar applications; Transponders; Pulse compression radar; radar cross-section (RCS); synthetic aperture radar (SAR); transponder

FOV-based model predictive object tracking for quadcopters - Snobar, Fadi; Reinhard, Johannes; Huber, Hartwig; Hoffmann, Marcel; Stelzig, Michael; Vossiek, Martin; Graichen, Knut (9th IFAC Symposium on Mechatronic Systems (Mechatronics 2022), 2022)

Potential of a Multimodal Orbital Radar Mission for the Exploration of Enceladus - Benedikter, Andreas; Rodriguez-Cassola, Marc; Krieger, Gerhard; Scheiber, Rolf; Martin del Campo Becerra, Gustavo; Horn, Ralf; Stelzig, Michael; Moreira, Alberto; Vossiek, Martin (EGU General Assembly 2020, 2020)
An Enceladus mission launched within a realistic time frame (e.g., launch between 2025 and 2040 and a transfer time of about ten years) would likely arrive as the sun is departing or gone from the most interesting South Polar Region marked by its active jets erupting through the ice crust. This almost drives the need for a radar instrument enabling the imaging, mapping and characterization of the moon independent of sunlight illumination. The known ice penetration capability of radar waves in the tens of MHz up to few GHz range allows for the exploration of subsurface features, whereas the surface may be imaged with high level of detail in higher frequencies up to several tens of GHz. In the frame of the Enceladus Explorer Initiative (EnEx) of the German Aerospace Center (DLR), we are currently investigating the potential of a multimodal orbital radar instrument to be used as a companion to a lander mission and to contribute in the understanding of the structure, composition and temporal variation of the Enceladean ice crust and the involved geophysical processes. The considered orbit geometries, strongly constrained by the presence of Saturn, allow for global coverage and offer half-daily revisit of the South Polar Region. We suggest a multi frequency system working concurrently in high frequency (e.g., Ka-band) and lower frequency (e.g., P-band) for surface and subsurface exploration, respectively, both capable of operating in a variety of modes: i) high resolution imaging used as a synthetic aperture radar (SAR), ii) SAR interferometer for topography, permittivity and surface and volume deformation estimates, iii) nadir looking configuration operating as an altimeter for elevation estimates and as a sounder for subsurface exploration with great penetration capability, iv) radiometer for surface temperature estimates and inversion of temperature profiles, and v) bistatic measurements between the radar instrument and an ice penetrating probe deployed by the lander with similarities to the CONSERT instrument of ESA's Rosetta mission. In this presentation, we evaluate the potential of the different modes concerning their scientific output and their usefulness for supporting the success of a lander mission. In particular the performance of SAR imaging and interferometry (single- and repeat-pass) modes are analysed, which are expected to provide key information for landing site selection such as structure, composition and topography of the surface and subsurface with metric resolution. For validation, we present results of a SAR campaign conducted using DLR's airborne sensor F-SAR over an alpine glacier, with simultaneous X- and L-band acquisitions. The campaign incorporates repeat- and single-pass acquisitions, as well as circular flights, which provide interferometric and tomographic measurements with observation geometries similar to those of an Enceladus mission. Furthermore, we provide an analysis towards a bistatic sounding experiment. Utilizing the transmission line between the radar instrument and a transponder integrated in an ice penetrating probe allows for the inversion of the spatial distribution of the dielectric ice properties and associated geophysical parameters (e.g., density, grain size, temperature, and salinity).

Radar-Based Recognition of Static Hand Gestures in American Sign Language - Schüßler, Christian; Zhang, Wenxuan; Bräunig, Johanna; Hoffmann, Marcel; Stelzig, Michael; Vossiek, Martin (2024 IEEE Radar Conference, 2024)
In the fast-paced field of human-computer interaction (HCI) and virtual reality (VR), automatic gesture recognition has become increasingly essential. This is particularly true for the recognition of hand signs, providing an intuitive way to effortlessly navigate and control VR and HCI applications. Considering increased privacy requirements, radar sensors emerge as a compelling alternative to cameras. They operate effectively in low-light conditions without capturing identifiable human details, thanks to their lower resolution and distinct wavelength compared to visible light. While previous works predominantly deploy radar sensors for dynamic hand gesture recognition based on Doppler information, our approach prioritizes classification using an imaging radar that operates on spatial information, e.g. image-like data. However, generating large training datasets required for neural networks (NN) is a time-consuming and challenging process, often falling short of covering all potential scenarios. Acknowledging these challenges, this study explores the efficacy of synthetic data generated by an advanced radar ray-tracing simulator. This simulator employs an intuitive material model that can be adjusted to introduce data diversity. Despite exclusively training the NN on synthetic data, it demonstrates promising performance when put to the test with real measurement data. This emphasizes the practicality of our methodology in overcoming data scarcity challenges and advancing the field of automatic gesture recognition in VR and HCI application
Keywords: Hand Gesture Recognition; Microwave Imaging; Machine Learning; Radar Simulation; Ray Tracing

SAR Interferometric and Tomographic Imaging of Saturn’s Moon Enceladus Using Strongly Perturbed Orbits - Benedikter, Andreas; Krieger, Gerhard; Rodríguez-Cassolà, Marc; Hussmann, Hauke; Wickhusen, Kai; Stark, Alexander; Stelzig, Michael; Vossiek, Martin (EUSAR 2022; 14th European Conference on Synthetic Aperture Radar, 2022)
In the frame of DLR’s Enceladus Explorer Initiative, we explore the potential of a SAR interferometric and tomographic orbiter for topography and deformation measurements, as well as 3-D imaging of the Enceladus ice crust. The stringent repeating ground track requirement for forming interferometric repeat-pass baselines paired with the strong gravitational perturbation by Saturn largely constrains the solutions for candidate orbits. Potential orbits have varying repeat-pass baselines between tens of meters and few kilometers. We assess the potential of a dual-frequency SAR instrument (Ka- and P-band) based on such orbits for repeat-pass SAR interferometry and tomography and provide first performance estimate

Taking a Look Beneath the Surface: Multicopter UAV-Based Ground-Penetrating Imaging Radars - Grathwohl, Alexander; Stelzig, Michael; Kanz, Julian; Fenske, Patrick; Benedikter, Andreas; Knill, Christina; Ullmann, Ingrid; Hajnsek, Irena; Moreira, Alberto; Krieger, Gerhard; Vossiek, Martin; Waldschmidt, Christian (IEEE Microwave Magazine, 2022)
The field of multicopter unmanned aerial vehicles (UAVs) has seen massive technological advances and decreasing costs over the last decade. Due to the higher prevalence and availability of these multicopter UAVs, there have also been rapid improvements in the software interfaceability, enabling the easy integration of custom software for flight planning and controllers. This opened up completely new possibilities, such as low-cost individual aerial photography, the most common civilian application. Furthermore, lightweight multicopters became widely accessible to the public, boosting the development of UAVs even more.<br

The TRIPLE Melting Probe - an Electro-Thermal Drill with a Forefield Reconnaissance System to Access Subglacial Lakes and Oceans - Heinen, Dirk; Audehm, Jan; Becker, Fabian; Böck, Georg; Espe, Clemens; Feldmann, Marco; Francke, Gero; Friend, Pia; Haberberger, Niklas; Helbin, Klaus; Nghe, Chi Thanh; Stelzig, Michael; et al. (OCEANS 2021: San Diego – Porto, 2021)
Recent measurements suggest the Jovian satellite Europa as one of the most promising places to host extraterrestrial life. Its global ocean is well hidden by a kilometer-thick layer of ice. Many currently discussed space missions therefore aim to explore Europa.The TRIPLE projects, initiated by the DLR Space Administration, comprise the development of Technologies for Rapid Ice Penetration and subglacial Lake Exploration, and consists of three components: (i) a melting probe, that travels through the ice and carries (ii) a small autonomous underwater vehicle (nanoAUV) that explores the ocean and takes samples to be delivered to (iii) an astrobiological laboratory. The full system should be demonstrated in a terrestrial analog mission in Antarctica in about five years. For a successful demonstration we need a retrievable melting probe capable of penetrating several kilometres of ice while avoiding obstacles and navigating around them. It has to be able to stop and dwell at the icewater boundary, before returning back to the surface. Within the projects TRIPLE-IceCraft and TRIPLE-FRS key technologies of such a melting probe are developed.The TRIPLE-IceCraft melting probe is designed as a modular system transporting standardised payloads through ice sheets of several hundred meters of thickness and penetrating into a subglacial water reservoir. Possible payloads are e.g. the nanoAUV or in-situ analysis devices for water samples such as a fluorescence spectrometer. The melting probe will be demonstrated at the Ekstrom shelf ice in Antarctica at the end of the project early 2023.The forefield reconnaissance system developed within TRIPLE-FRS combines radar and sonar techniques to benefit from both sensor principles inside ice. The radar antennas together with a specialized pulse amplifier as well as a piezoelectric acoustic transducer will be integrated into the melting head. To account for the respective propagation speed of electromagnetic waves, an in-situ permittivit...<br

Towards the Validation of a Volumetric Imaging Concept for the SAR Exploration of Enceladus - Benedikter, Andreas; Rodriguez-Cassola, Marc; Krieger, Gerhard; Scheiber, Rolf; Martin del Campo Becerra, Gustavo; Horn, Ralf; Moreira, Alberto; Stelzig, Michael; Vossiek, Martin (AGU Fall Meeting 2019, 2019)

Virtual Synthetic Aperture Radar Target Based on a Miniaturized Monostatic Digital Delay Transponder - Stelzig, Michael; Benedikter, Andreas; Horn, Ralf; Jaeger, Marc; Keller, Martin; Scheiber, Rolf; Krieger, Gerhard; Vossiek, Martin (IEEE Microwave and Wireless Components Letters, 2021)
The ice penetrating capability of low-frequency radar systems may offer a unique potential for the detection, localization, and guidance of exploratory ice-penetrating probes for cryospheric applications. As these probes exhibit a comparably small radar cross section (RCS), reliable detection, especially in high clutter surroundings, such as ice sheets, is prevented. As a solution, a miniaturized monostatic digital delay transponder is developed and tested regarding its functionality with an airborne synthetic aperture radar (SAR) sensor.
Keywords: Transponders; Radar; Syntethic aperture radar (SAR); Radar cross-sections (RCS); Delays; Probes; Ice; Pulse compression